Quasi-Radical Semiprime Submodules - Al-Ragab, Omar M; Al-Mothafar, Nuhad S. (Iraqi Journal of Science, 2022)
In this paper, we introduce the concept of a quasi-radical semi prime submodule. Throughout this work, we assume that    is a commutative ring with identity and  is a left unitary R- module. A  proper submodule  of  is called a quasi-radical semi prime submodule (for short Q-rad-semiprime), if     for   ,   ,and then  . Where   is the intersection of all prime submodules of .